A Perfect Storm? The collapse of Lancaster's critical infrastructure networks following intense rainfall on 4/5 December 2015. (January 2017) - Ferranti, Emma; Chapman, Lee; Whyatt, Duncan
Abstract : On 4/5 December 2015 a slow moving frontal system associated with the extratropical cyclone Storm Desmond brought record‐breaking levels of rainfall to Lancaster. Both high ground and low‐lying areas were already saturated following the wettest November on record, and on the evening of 5 December the River Lune flooded into the city. Critical road and rail transport networks ground to a halt, and the city and the surrounding areas were left without mains power for 2 days after a key substation flooded, consequently leaving the majority of communication services inoperable. Was this a 'Perfect Storm', or a glimpse of what the future may hold for our cities as they face more frequent extreme weather events, set against the backdrop of urban population growth, and increasingly interdependent critical urban infrastructure systems?